QUALITY OF LIFE OF PATIENTS WITH SARCOMA AFTER CONSERVATIVE SURGERY OR AMPUTATION OF LIMBS - Silva, Rogério Santos (Acta Ortop Bras, 2019)
OBJECTIVE: To conduct an integrative review on quality of life (QOL) of patients with sarcoma who underwent conservative surgery or limb amputation. METHODS: We conducted a six-step integrative review by searching the databases LILACS, SciELO, PePSIC, Embase, and PubMed, using the descriptors: “Quality of life”, “Bone cancer”, “Sarcoma”, “Limb Salvage,” and “Amputation.” Ten studies were selected according to: database, type of study, methods, researcher's profession, sex, histological type, title, country/region, and periodical/year of publication. RESULTS: Nine quantitative and one qualitative studies were included. All were conducted by physicians and correlated to QOL with the impact of diagnosis, psychosocial aspects, cancer treatment, and survival. Other aspects included type of surgery, functionality, rehabilitation, and a multidisciplinary approach. The QOL results were similar for conservative surgery and amputation in eight studies. In two, it was concluded that patients undergoing conservative surgery had a better QOL. CONCLUSION: The number of studies on QOL in patients with sarcoma is small. In most, there was no difference between the study groups. In addition, the studies indicated the importance of evaluation of QOL, since it has a direct effect on patients' physical manifestations and impacts their coping abilities. Level of evidence III, System review.